EFFICIENT, SCALABLE, AND MULTI-PATH NETWORK MOBILITY MANAGEMENT SCHEMES FOR MOBILE NETWORKS - WAGAN, ASIF ALI (2018)
The Network Mobility Basic Support Protocol (NEMO-BSP) is an extended version of Mobile Internet Protocol (MIPv6) designed to support seamless communications between homogenous and heterogeneous network domains. NEMOBSP is a basic mobility solution that lacks good QoS, specifically in terms of packet delivery cost and end-to-end delay.